2021
DOI: 10.1007/s10644-021-09351-7
|View full text |Cite
|
Sign up to set email alerts
|

Japan-US bilateral commodity-level trade and trade policy-related uncertainty under the COVID-19 pandemic: the nonlinear ARDL model

Abstract: This study examines whether t rade p olicy-related u ncertainties, scaled by TPU index, and the COVID-19 pandemic affect Japan’s bilateral commodity trade balance with the U.S concerning 60 industries. To this end, the nonlinear ARDL (autoregressive distributed lag) model is applied. Empirical findings of the disaggregated data model indicate that while changes in Japan’s TPU index have significant, either improving or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The third research area focused on the demand for industrial goods, foodstuff trade, and the corresponding supply chains. Ongan and Gocer (2022) studied the connection between the COVID-19 pandemic and the Japan-USA trade about the production of 60 industrial branches. The study applied an autoregressive distributed lags model to analyze the effect of the economic measures through the Trade Policy Uncertainty (TPU) index and found that its influence was country-dependent -more substantial in the USA than in Japan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The third research area focused on the demand for industrial goods, foodstuff trade, and the corresponding supply chains. Ongan and Gocer (2022) studied the connection between the COVID-19 pandemic and the Japan-USA trade about the production of 60 industrial branches. The study applied an autoregressive distributed lags model to analyze the effect of the economic measures through the Trade Policy Uncertainty (TPU) index and found that its influence was country-dependent -more substantial in the USA than in Japan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It should be noted that the empirical findings of this study should be considered and interpreted within this assumption. The term euro area is used to describe the member countries of the European Union (EU) that use the Euro (€) as their national currency.6 This index is used in a wide range of studies(Bahmani-Oskooee and Saha (2017); Bahmani-Oskooee and Durmaz (2020);Ongan and Gocer (2021b).Review of Economic Analysis forthcoming (14) 2022 www.RofEA.org…”
mentioning
confidence: 99%